Against Inequality : Contributions to a Discourse of Social Emancipation - Canales, Alejandro, (Social Sciences E-Books Online, Collection 2025., 2025)
In Against Inequality , the authors offer a theoretical and political proposal for social emancipation, seen as an opportunity to build conditions of equality in contexts of freedom, not only for ethical but essentially political foundations. To achieve this, the authors confront inequality in two ways: as a social phenomenon (and, therefore, historically situated and structured) and through critical reflection on the concepts, categories, indicators and frameworks of its understanding. In this sense, they propose a critical reflection of the ways in which it has been thought theoretically and politically at various times, with special reference to the way in which it has been conceived in modern, capitalist society.